Jaime Edmundo Rodríguez Ordóñez (1940-2022) - Peralta Ruiz, Víctor (2022)
Jaime Edmundo Rodríguez Ordóñez was, beyond doubt, one of Latin America’s most outstanding historians. This note provides a biographical portrait and describes his key contribution to the understanding of South American independence. Jaime Rodríguez’s production was wide-ranging and always in dialogue with Latin American and European historiography.